2017
DOI: 10.1093/pm/pnx178
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Opioid Therapy: Distinguishing Clinical Characteristics and Demographics Among Patients with Cancer Pain

Abstract: History of ETOH use, anxiety, high SOAPP-SF score, and younger age were associated with UDT that indicates noncompliance. Given the very small percentage of UDT testing, it is quite likely that a significant number of patients who did not undergo UDT were also nonadherent with treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Regarding the drug, other researches show that adherence can vary even among active principles, given the occurrence of posological variations and adverse reactions, which are frequent with the use of opioids and which tend to predispose to nonadherence. 5,12,13 In this study, besides the large number of patients who scored in the reminder domain, a significant association was noted between patients who used a controlled-release (CR) drug and the adherence, a fact that may be correlated with better ease in administering this type of pharmaceutical form, information also observed by Meghani et al 20 Furthermore, as seen by Zhu and et al, patients with better educational levels presented a positive association with therapeutic adherence. 14 Believing in the therapy is a great facilitator for adherence, but the presence of symptoms and adverse effects can affect it negatively.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding the drug, other researches show that adherence can vary even among active principles, given the occurrence of posological variations and adverse reactions, which are frequent with the use of opioids and which tend to predispose to nonadherence. 5,12,13 In this study, besides the large number of patients who scored in the reminder domain, a significant association was noted between patients who used a controlled-release (CR) drug and the adherence, a fact that may be correlated with better ease in administering this type of pharmaceutical form, information also observed by Meghani et al 20 Furthermore, as seen by Zhu and et al, patients with better educational levels presented a positive association with therapeutic adherence. 14 Believing in the therapy is a great facilitator for adherence, but the presence of symptoms and adverse effects can affect it negatively.…”
Section: Discussionsupporting
confidence: 72%
“…Although not observed in this study, the literature also shows that female gender, younger age, and black ethnicity may be associated with less commitment to the drug treatment, the latter mainly due to demographic and access differences to the drug. 7,12,13 In parallel, in other studies, a lower financial condition seems to be a negative factor for continuing treatment. 12,14…”
Section: Rbfhss Revista Brasileira De Farmácia Hospitalar E Serviços De Saúdesupporting
confidence: 51%
“…7 The authors did not speculate as to the reasons for sex differences in ECS compliance. Cigarette smoking has been found to be a predictor of noncompliance with prescribed therapy across several fields of research, [8][9][10][11][12][13][14][15][16] and smoking cessation has been reported to be predictive of increased adherence to therapy. 17 To our knowledge, cigarette smoking has not previously been reported as a predictor of noncompliance with compression stocking use.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reporting on the frequency of abnormal UDT in patients with cancer were conducted with a purposefully selected sample of patients with an already known elevated risk of NMOU, and this raises questions about a potential selection bias. Such studies may, therefore, not be reflective of the true frequency in this patient population 18,23,31‐33 . We acknowledge that the cohort in our study consisted of patients referred to a supportive care clinic with a relatively high level of symptom burden and distress and may, therefore, be more inclined to have a higher risk for NMOU than the average oncology patient.…”
Section: Discussionmentioning
confidence: 98%